Characterization of the Carbonate Reservoir Unit A of the Upper Triassic Kurra Chine Formation in the well SH-4, Shaikan Oilfield, Iraqi Kurdistan Region, Using Wireline Log Data - Dler H. Baban; Mostafa M. Ahmed (Tikrit Journal of Pure Science)
Unit A of Kurra Chine Formation has been studied in the well Shaikan - 4 (SH-4) at Shaikan Oilfield in Northern Iraqi Kurdistan Region. The available conventional wireline log data and the existed core test values have been used to characterize the reservoir properties of the studied unit and to determine the flow efficiency of the reservoired fluids. The dolomite and anhydrite dominated lithology of the studied unit contains low percentages of shale except the upper most part of the unit in which shale content exceeds 30%. The porosity is less than 5% in most parts of the unit and secondary porosity comprises less than 4% of the total porosity in some horizons. The shale content consists primly of Illite and Chlorite and distributes in a dispersed pattern. Hydrocarbons are exist almost along the studied unit in saturations exceeding 70% at the middle and lower part of the unit. No effective permeable intervals observed at the upper part of the unit, whereas permeable zones of greater than 70mD are observed at the lower part. Three reservoir units distinguished in Kurra Chine A unit based on variations in shale content, porosity, and permeability. The studied unit contains four distinctive types of Hydraulic Flow Units (HFU) of less than 2.0, 20-5.5, 5.5-10, and greater than 10 Flow Zone Indicator (FZI) values. The calculated net to gross pay ratio for the studied Kurra Chine A Unit appeared to be about 28% representing the collective 52m net pay to the 184m gross thickness of the studied A Unit.